Analysis of the organizational eco-systemic change in a cooperative society of fishing production - José G. Vargas-Hernández; Julieta Elizabeth Salazar Echeagaray; Teresa Irina Salazar Echeagaray (Atlantic Review of Economics, 2016)
This work aims to analyze the organizational change that has taken the Cooperative Society of Fishing Production "The Patole", S.C. of R.L. de C.V. It is assumed that as a result of having implemented systems theory, it has improved its organizational development and thus fulfillment of its objectives, being a source of employment and income for the cooperative. The rmain method used in this analysis is observing partners, gathering factual information and indicators and supported by the application of a Likert scale questionnaire. It is concluded that systems theory is related to the cooperative to be beneficial in the organizational development of the company.
Keywords: Q22; I10; l26; M13; B41; 330; Organizational Change; fisheries production cooperatives; systems theory